Never say die - Hobbs, Will (Harper, 2014)
Fifteen-year-old half-Inuit Nick and his white brother, Ryan, meet and share an adventure on the Firth River in the Canadian Arctic, facing white water, wild animals, and fierce weather as Ryan documents the effects of climate change on caribou for National Geographic magazine.